Socio-Linguistic Patterns in Multilingual Bukhara: An Analysis across Four Languages - Tagaeva Feruza Erkinovna (Researchparks Publishing, 2023)
This study embarks on an exploratory journey into the intricate socio-linguistic landscape of Bukhara, a region historically and culturally rich, yet academically underexplored in terms of its multilingual dynamics. Central to this research is the analysis of linguistic patterns emerging from the interaction of four predominant languages in Bukhara, delving into a realm where cultural interplay and linguistic diversity coalesce. Utilizing a mixed-methods approach, combining qualitative techniques such as ethnographic observations and in-depth interviews with quantitative methods like linguistic surveys, the study dissects the complex socio-linguistic interactions that underpin the everyday communication in this multilingual milieu. The findings unearth distinctive linguistic behaviors and attitudes, elucidating how historical, cultural, and social influences have sculpted the current linguistic landscape. This research contributes novel insights into the understanding of multilingualism, not merely as a linguistic phenomenon but as a socio-cultural tapestry, offering a nuanced perspective on how language functions in a multilayered societal context. The implications of this study extend beyond the boundaries of linguistic theory, providing a window into the socio-cultural dynamics of multilingual societies and laying the groundwork for future interdisciplinary research in this field.This study embarks on an exploratory journey into the intricate socio-linguistic landscape of Bukhara, a region historically and culturally rich, yet academically underexplored in terms of its multilingual dynamics. Central to this research is the analysis of linguistic patterns emerging from the interaction of four predominant languages in Bukhara, delving into a realm where cultural interplay and linguistic diversity coalesce. Utilizing a mixed-methods approach, combining qualitative techniques such as ethnographic observations and in-depth interviews with quantitative methods like linguistic surveys, the study dissects the complex socio-linguistic interactions that underpin the everyday communication in this multilingual milieu. The findings unearth distinctive linguistic behaviors and attitudes, elucidating how historical, cultural, and social influences have sculpted the current linguistic landscape. This research contributes novel insights into the understanding of multilingualism, not merely as a linguistic phenomenon but as a socio-cultural tapestry, offering a nuanced perspective on how language functions in a multilayered societal context. The implications of this study extend beyond the boundaries of linguistic theory, providing a window into the socio-cultural dynamics of multilingual societies and laying the groundwork for future interdisciplinary research in this field.